Differentiation Based on the Value of Business Relations: How to Reach and Maintain the Provider Status. An Analysis of the Buyer-Seller Relationship in an Emerging Economy. - Gudziol-Vidal, Juan Antonio; Buenaventura-Vera, Guillermo (Journal of Applied Business and Economics, 2018)
The present work aims to establish the characteristics that importers (buyers) consider of value when choosing their international suppliers (vendors) and based on the interrelations of these characteristics. We propose an empirical relationships model, contrasted by Structural Equations Modeling (SEM), tested using AMOS. The results confirm several relationships of the model.